Psychological Analysis of the Perspectives on Stigma among Teenagers with Mental Disorders - Rajgun Handique, Manish Tyagi, Jaykumar Padmanabhan (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Objectives: To determine target demographics and cultural factors for future anti-stigma activities, differences in the Stigma associated with mental illness (MI) between teenagers were explored cross-sectional through race, gender, and ethnicity. Methods: Sixth graders from a variety of racial and socioeconomic backgrounds (N=558; Average Age=12.8) self-reported their understanding of MI, attitudes toward peers who have the disease, and behaviors towards those peers as well as towards two adolescent featuring bipolar (Person A) and social anxiety (Person B) signs. Six intersecting composite variables were created using self-reported data on racial, ethnic, and gender characteristics: Boys and girls who are Latino, Latina, Non-Latina/o (NL) Black, White, NL-Black, and NL-White referent. Utilizing distinct and combined race, ethnicity, and gender variables, linear regression methods controlling for personal and family features looked at variations in Stigma. Results: Correspondingly, boys and Latino/teenagers observed more Stigma for different outcomes in main effects models than girls and NL-white teenagers. But intersectional analysis uncovered distinctive designs. NL-black males indicated a lesser amount of knowledge and optimistic attitudes than NL-black and white girls. NL-black and Latino guys showed more prevention and distress than NL-white girls. In addition, NL-black boys expressed a desire for greater social isolation from their peers who had mental illnesses, unlike NL-white girls. In contrast to NL-black boys, NL-white boys, and NL-black boys, Latina females expressed a desire for greater solitude. More distance from Person B was also chosen by NL-black men and NL-Latina women compared to NL-white boys and NL-black women. Conclusions: This research contributes novel data regarding the ways in which beliefs about MI vary according to racial and ethnic identity and the ways in which gender overlaps with these perspectives, information that will be crucial for guiding future anti-stigma initiatives.